2022
DOI: 10.1021/acsabm.2c00349
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Fingolimod (FTY720) Anti-SARS-CoV-2 Activity Using a PLGA-Based Drug Delivery System

Abstract: COVID-19 has resulted in more than 490 million people being infected worldwide, with over 6 million deaths by April 05th, 2022. Even though the development of safe vaccine options is an important step to reduce viral transmission and disease progression, COVID-19 cases will continue to occur, and for those cases, efficient treatment remains to be developed. Here, a drug repurposing strategy using nanotechnology is explored to develop a therapy for COVID-19 treatment. Nanoparticles (NPs) based on PLGA for fingo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…The NPs were fabricated through a single emulsion solvent evaporation technique, resulting in a positively charged system with reported sizes of approximately 400 and 190 nm for empty NPs and FTY720-NP, respectively. The system demonstrated a notable drug entrapment rate of 90%, with drug release being contingent upon pH [75]. The study found that drug release required an acidic environment, which the developed NPs can access through caveolin-mediated endocytosis and micropinocytosis pathways.…”
Section: Plgamentioning
confidence: 95%
“…The NPs were fabricated through a single emulsion solvent evaporation technique, resulting in a positively charged system with reported sizes of approximately 400 and 190 nm for empty NPs and FTY720-NP, respectively. The system demonstrated a notable drug entrapment rate of 90%, with drug release being contingent upon pH [75]. The study found that drug release required an acidic environment, which the developed NPs can access through caveolin-mediated endocytosis and micropinocytosis pathways.…”
Section: Plgamentioning
confidence: 95%
“… 163 Lopinavir (LPV), an antiviral drug, could be loaded into PLGA nanoparticles coated with macrophage membranes (PLGA-LPV@M) to reduce tissue viral loads in mouse models. 164 Other anti-inflammatory and antiviral drugs, such as celecoxib, 165 quinine, 166 oseltamivir-phosphate, 167 favipiravir, 168 and fingolimod, 169 could be coated on or encapsulated into PLGA polymeric nanoparticles.…”
Section: Biomaterials Help To Anti-sars-cov-2 Strategiesmentioning
confidence: 99%
“…Targeted delivery of antibiotics loaded to PLGA particles has been described in several studies to effectively treat bacterial infections and reduce the risk of resistance development [ 149 , 150 , 151 ]. In a similar fashion, encapsulation and delivery of anti-viral and immunomodulating drugs have been successfully explored using PLGA particles to fight viral infections [ 152 , 153 , 154 , 155 ]. Aside from the aforementioned tools for approaching infectious diseases, protective vaccinations represent one of the most effective medical tools up to date.…”
Section: Most Successful Application Of Plga Particles In Immunotherapymentioning
confidence: 99%